N-Feruloylserotonin inhibits lipopolysaccharide-induced inflammation via SIRT1-stimulated FOXO1 and NF-κB signaling pathways in RAW 264.7 cells: Anti-inflammatory effect of N-feruloylserotonin - Park, Chan Hum; Han, Sung Woo; Seong, Su Hui; Choi, Jae Sue; Jeon, Jin Pyeong; Yokozawa, Takako (Cellular and Molecular Biology, 2023)
Macrophages become activated by a variety of stimuli such as lipopolysaccharide (LPS) and participate in the process of immune responses. Activated macrophages produce various inflammatory mediators. In the present study, we investigated the anti-inflammatory mechanism of a serotonin derivative, N-feruloylserotonin, isolated from safflower seeds in RAW 264.7 macrophages. N-Feruloylserotonin treatment significantly attenuated these effects on LPS-induced reactive oxygen species, nitric oxide, and prostaglandin E2 production in RAW 264.7 macrophages. Furthermore, N-feruloylserotonin significantly decreased the abnormal expression of mitogen-activated protein kinase, such as phosphor (p)-c-Jun N-terminal kinase and p-extracellular-signal regulated kinase activation. Further research revealed that N-feruloylserotonin could stimulate sirtuin1 (SIRT1), then promote the forkhead box protein O1 (FOXO1), and suppress nuclear factor-kappa B (NF-kB) signaling pathways. The present study suggests that N-feruloylserotonin may be a new anti-inﬂammatory component and a promising candidate for anti-inflammatory therapeutic agents through the regulation of SIRT1-stimulated FOXO1 and NF-kB signaling pathways.